2004
DOI: 10.1093/biostatistics/5.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Detecting differential gene expression with a semiparametric hierarchical mixture method

Abstract: Mixture modeling provides an effective approach to the differential expression problem in microarray data analysis. Methods based on fully parametric mixture models are available, but lack of fit in some examples indicates that more flexible models may be beneficial. Existing, more flexible, mixture models work at the level of one-dimensional gene-specific summary statistics, and so when there are relatively few measurements per gene these methods may not provide sensitive detectors of differential expression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
519
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 546 publications
(532 citation statements)
references
References 28 publications
2
519
0
1
Order By: Relevance
“…As recently demonstrated at a gene-specific level (Lo and Gottardo, 2007), an accurate modeling of residual dispersion patterns allows for a more realistic fit of gene expression data, reducing the rate of false positives when differential gene expression is characterized in terms of mathematical expectations or their differences (Kendziorski et al, 2003;Newton et al, 2004;Lo and Gottardo, 2007). Moreover, the analysis of heterogeneous residual dispersion patterns opens up promising research possibilities within the gene expression framework, where heterogeneity in residual variability could be viewed as an alternative and plausible characterization of differential expression patterns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As recently demonstrated at a gene-specific level (Lo and Gottardo, 2007), an accurate modeling of residual dispersion patterns allows for a more realistic fit of gene expression data, reducing the rate of false positives when differential gene expression is characterized in terms of mathematical expectations or their differences (Kendziorski et al, 2003;Newton et al, 2004;Lo and Gottardo, 2007). Moreover, the analysis of heterogeneous residual dispersion patterns opens up promising research possibilities within the gene expression framework, where heterogeneity in residual variability could be viewed as an alternative and plausible characterization of differential expression patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Assuming null residual (co)variances (Kendziorski et al, 2003;Newton et al, 2004;, heteroskedasticity between physiological stages was analyzed by stating…”
Section: Methodsmentioning
confidence: 99%
“…Theoretical connection among various ranking methods, including those based on hierarchical Bayesian models (Newton et al, 2004;Noma et al, 2010), and comparison of their performances are important research areas. Recently, Storey (2007) developed the optimal discovery procedure, an optimality criterion for ordering tests in multiple testing, which can be formulated as a multiple test extension of the Neyman-Pearson optimality for testing individual genes.…”
Section: Discussionmentioning
confidence: 99%
“…Optimality of gene ranking is, hence, an important research area in statistical analysis of microarray studies. Recently, Newton et al (2004) and McLachlan et al (2006) have shown a ranking based on the local false discovery rate (local FDR; Efron et al, 2001), which represents the posterior probability of non-differential expression of each gene, is optimal for selecting differentially expressed genes from the viewpoint of the Bayesian decision theory. More recently, Noma et al (2010) developed three empirical Bayes methods for gene ranking on the basis of differential expression, using hierarchical mixture models.…”
Section: Introductionmentioning
confidence: 99%
“…Using this scale-free, univariate probability score, one can call peptide assignments correct if posterior probability is above a certain threshold. This posterior probability is directly related to local false discovery rate (fdr) discussed in Efron et al 12 and Newton et al, 13 and thus specifying the minimum probability threshold automatically controls global FDR to a desired degree.…”
Section: Introductionmentioning
confidence: 99%